1993
DOI: 10.1136/ard.52.10.749
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the rat oesophagus epithelium antigens defined by the so-called 'antikeratin antibodies', specific for rheumatoid arthritis.

Abstract: Objectives-An attempt was made to characterise the antigens recognised by serum IgG antibodies directed to the stratum corneum of rat oesophagus epithelium, the so-called 'antikeratin antibodies', which were shown to be highly specific for rheumatoid arthritis (RA) and thus to have an actual diagnostic value. Methods-Immunoblotting was performed with RA serum samples on different extracts of rat oesophagus epithelium separated by various monodimensional and two dimensional electrophoreses. Results-Three low-sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 42 publications
0
27
0
1
Order By: Relevance
“…The occurrence of ACPAs early in the disease course and even before the onset of clinical symptoms (7,8), as well as the correlation with disease severity and prognosis (9,10), suggests that ACPAs are not only valuable clinical biomarkers but are also pathophysiologically involved in the disease. However, epithelial (pro)filaggrin, which is the first identified antigenic target of ACPAs (11)(12)(13), is not expressed in the joint and RA does not affect filaggrin-containing epithelial tissues, such as skin and buccal mucosa. Based on crucial observations that ACPAs can be produced locally in the joint (14) and that posttranslational modification of arginine into citrulline residues in the context of specific amino acid sequences is essential for recognition by ACPAs (15)(16)(17), the assumption was made that citrullinated filaggrin could be a cross-reacting in vitro antigen rather than a genuine in vivo antigenic target of ACPAs and, subsequently, that distinct citrullinated proteins present in the inflamed synovium may be involved in the induction or perpetuation of the RA-specific humoral autoimmune responses.…”
mentioning
confidence: 99%
“…The occurrence of ACPAs early in the disease course and even before the onset of clinical symptoms (7,8), as well as the correlation with disease severity and prognosis (9,10), suggests that ACPAs are not only valuable clinical biomarkers but are also pathophysiologically involved in the disease. However, epithelial (pro)filaggrin, which is the first identified antigenic target of ACPAs (11)(12)(13), is not expressed in the joint and RA does not affect filaggrin-containing epithelial tissues, such as skin and buccal mucosa. Based on crucial observations that ACPAs can be produced locally in the joint (14) and that posttranslational modification of arginine into citrulline residues in the context of specific amino acid sequences is essential for recognition by ACPAs (15)(16)(17), the assumption was made that citrullinated filaggrin could be a cross-reacting in vitro antigen rather than a genuine in vivo antigenic target of ACPAs and, subsequently, that distinct citrullinated proteins present in the inflamed synovium may be involved in the induction or perpetuation of the RA-specific humoral autoimmune responses.…”
mentioning
confidence: 99%
“…Among them, rheumatoid factors have been the most extensively studied (reviewed in reference 1), but numerous other autoantibodies such as anticollagen (2), antinuclear (3,4), and anticytoskeletal (5) antibodies have been described. A lot of work has also been performed on the antiperinuclear factor (APF)' (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)) and on the antikeratin antibodies (AKA) (9,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Both these antibodies have been demonstrated to be highly specific serological markers of the disease and therefore are increasingly used for the diagnosis of RA (reviewed in reference 38).…”
Section: Introductionmentioning
confidence: 99%
“…3 They were first referred to as antifilaggrin autoantibodies (AFA), which encompass two IgG autoantibody families, the socalled antikeratin Abs and the antiperinuclear factor. Indeed, several decades after their initial, independent descriptions, we showed that both anti-keratin Abs and antiperinuclear factor recognize diverse forms of the squamous epithelium protein, filaggrin, or of its precursor, profilaggrin (1)(2)(3), and demonstrated that they constitute largely overlapping autoantibody families (3). We also showed that the filaggrin-related targets of AFA correspond to deiminated proteins, of which arginyl residues have been posttranslationally transformed into citrullyl residues by a peptidylarginine deiminase (PAD) (4).…”
mentioning
confidence: 99%